2021
DOI: 10.3390/en14227513
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Length and Conductivity of Artificial Fracture on Gas Production from a Class 3 Hydrate Reservoir

Abstract: Natural gas hydrate is considered as a potential energy resource. To develop technologies for the exploitation of natural gas hydrate, several field gas production tests have been carried out in permafrost and continental slope sediments. However, the gas production rates in these tests were still limited, and the low permeability of the hydrate-bearing sediments is identified as one of the crucial factors. Artificial fracturing is proposed to promote gas production rate by improving reservoir permeability. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Hydraulic fracturing has become a prevalent technique in the oil and gas industry, 103−105 primarily leveraging technological interventions to induce artificial fractures within subterranean rock strata and natural gas reservoirs. 106,107 This process serves to enhance hydrocarbon recovery rates by facilitating increased fluid flow. 42,44,88,108 When examining the mechanical properties of HBS, the subsurface stress is a complex combination of radial, alonglayer, and vertical positions, and the triaxial instrument has the same peripheral pressure, which is unable to provide the displacement and deformation information related to other dominant stress directions, and cannot accurately simulate the real stress environment of the subsurface reservoirs.…”
Section: True Triaxial Testing Apparatusmentioning
confidence: 99%
“…Hydraulic fracturing has become a prevalent technique in the oil and gas industry, 103−105 primarily leveraging technological interventions to induce artificial fractures within subterranean rock strata and natural gas reservoirs. 106,107 This process serves to enhance hydrocarbon recovery rates by facilitating increased fluid flow. 42,44,88,108 When examining the mechanical properties of HBS, the subsurface stress is a complex combination of radial, alonglayer, and vertical positions, and the triaxial instrument has the same peripheral pressure, which is unable to provide the displacement and deformation information related to other dominant stress directions, and cannot accurately simulate the real stress environment of the subsurface reservoirs.…”
Section: True Triaxial Testing Apparatusmentioning
confidence: 99%
“…In addition, secondary hydrates formed in the fracturing areas of the low-temperature reservoirs. Shang et al 99 studied the fracture length and conductivity coefficient (the product of the fracture permeability and width). They found that the influence of the fracture length on the production performance depended on the length of the mining time, whereas increasing the fracture length did not show a good gas production effect in the early stages of mining.…”
Section: Stimulation Performance Of Hydraulicmentioning
confidence: 99%
“…10 Numerical studies about the effect of artificial fracturing on production performance are carried out in a Class 3 hydrate reservoir at the Mount Elbert Prospect on the Alaska North Slope. 31 The effects of hydraulic fracturing on the enhanced gas recovery were thoroughly investigated at the second test site in the South China Sea. 29…”
Section: Tough + Hydrate Local Grid Refinementmentioning
confidence: 99%
“…However, the current Tough+Hydrate simulator lacks a separate module that can explicitly represent fractures and calculate the mass and heat exchange between sediments and fractures. As shown in Table , a commonly used way to explicitly express fractures in the simulator is the scheme of local grid refinement (LGR) to depict fracture width. , Although this method is easy to implement, two issues arise: (1) its inability to construct fracture networks with complex distributions; (2) a large number of grids after local gird refinement around fractures, thereby slowing down the speed of computation. The former is a result of a simultaneous consideration of both sediments and fractures, while the latter is caused by the significant contrast in the scales of fracture width (a few millimeters to centimeters) and hydrate reservoirs (hundreds or even thousands of meters) …”
Section: Introductionmentioning
confidence: 99%